PROJECT-BASED LEARNING COMBINED WITH WHATSAPP APPLICATION TO DEVELOP STUDENTS’ WRITING SKILLS - I Nyoman Suwandi (Bajang Institute, 2021)
The project-based learning model is a learning model which in its implementation can teach students to master process skills and their application in everyday life. This learning model is the center of the learning strategy because students learn the main concepts of knowledge through project work. Project work is central to the learning activities carried out by students in the classroom. Project work carried out by students is based on questions or problems that lead students to find concepts about certain fields. Therefore, the activities become external motivation that can generate internal motivation in students to build independence in completing tasks. This study was conducted to leverage students’ writing skills through conducting the project-based study integrated with the WhatsApp application. This study revealed that students’ writing skills improve significantly from the first cycle and the second cycle after the implementation of project-based learning integrated with the WhatsApp application. This study implies that teachers should utilize project-based learning in teaching writing more intensively.